2015
DOI: 10.1074/jbc.m115.649202
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Bardet-Biedl Syndrome 9 Protein (BBS9)

Abstract: Background: BBS9 is a component of the octameric BBSome, a complex that transports membrane proteins to the primary cilium. Results: BBS9 has four folded domains, based on structure prediction; the N-terminal domain is a ␤-propeller. Conclusion: BBS9 likely acts as a scaffold component in the BBSome coat. Significance: The structural data help in understanding a mutation that causes Bardet-Biedl syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Both structural and mechanistic details of how the LIFT system binds the lipid anchors of cargo, and release these in the cilium, are emerging [59 , 62,63], although how the LIFT system enters the cilium remains to be determined. Breakthrough structural studies on IFT subcomplexes A and B [4,58 ,74,75], and BBS subunits [76,77] are helping to dissect the structural organization of the multi-subunit IFT particles. However, very little is known about how IFT proteins bind their cargo, with the very notable exception of tubulin [50 ,51].…”
Section: Box 1 Outstanding Questionsmentioning
confidence: 99%
“…Both structural and mechanistic details of how the LIFT system binds the lipid anchors of cargo, and release these in the cilium, are emerging [59 , 62,63], although how the LIFT system enters the cilium remains to be determined. Breakthrough structural studies on IFT subcomplexes A and B [4,58 ,74,75], and BBS subunits [76,77] are helping to dissect the structural organization of the multi-subunit IFT particles. However, very little is known about how IFT proteins bind their cargo, with the very notable exception of tubulin [50 ,51].…”
Section: Box 1 Outstanding Questionsmentioning
confidence: 99%
“…As previously described 24 , the b-propeller of BBS9 is negatively charged around its central cavity. Our structure reveals that it interacts with a positively charged patch of BBS8 ( Figure 3C).…”
Section: Surface Complementary B-propeller-tpr Interactionsmentioning
confidence: 79%
“…Since their structure is very similar, it can be imagined that these domains would induce selfdimerization of either BBS1 or BBS9. Indeed, in previous studies 24,26 , it was shown that the isolated C-terminal region of BBS9, including the GAE domain, forms a dimer in solution. A superposition of BBS9 monomers reveals that an interaction via their GAE domains would not result in steric clashes ( Figure S2C).…”
Section: The C-terminus Of Bbs9 Forms a Gae Binding Motifmentioning
confidence: 98%
See 1 more Smart Citation
“…These models were trimmed to remove unstructured or poorly 27 predicted regions. For BBS9 bprop , BBS1 bprop and ARL6, the crystal structures of human 28 BBS9 bprop (PDB accession code 4YD8) (Knockenhauer and Schwartz, 2015) and 29 Chlamydomonas reinhardtii BBS1 bprop :ARL6:GTP complex (PDB accession code 40VN) 30 (Mourão et al, 2014) were used directly and mutated to the Bos taurus sequence. The models 31 were then placed into the BBSome density map using the fit-to-map procedure in Chimera 1 (Pettersen et al, 2004) or manually in Coot v0.8.9 (Brown et al, 2015).…”
Section: Competing Information 28mentioning
confidence: 99%